The Dictyostelium homologue of mammalian soluble adenylyl cyclase encodes a guanylyl cyclase - Roelofs, Jeroen (Oxford University Press, 2001)
A new Dictyostelium discoideum cyclase gene was identified that encodes a protein (sGC) with 35% similarity to mammalian soluble adenylyl cyclase (sAC). Gene disruption of sGC has no effect on adenylyl cyclase activity and results in a >10-fold reduction in guanylyl cyclase activity. The scg– null mutants show reduced chemotactic sensitivity and aggregate poorly under stringent conditions. With Mn(2+)/GTP as substrate, most of the sGC activity is soluble, but with the more physiological Mg(2+)/GTP the activity is de tected in membranes and stimulated by GTPγS. Unexpectedly, orthologues of sGC and sAC are present in bacteria and vertebrates, but absent from Drosophila melanogaster, Caenorhabditis elegans, Arabidopsis thaliana and Saccharomyces cerevisiae.